Sponsorship of physical activity programs by the sweetened beverages industry: Public health or public relations? (2011)
The growing evidence on the association between consumption of sugar-sweetened beverages, obesity and other chronic diseases has highlighted the need to implement policy actions that go beyond programs exclusively focused on individual responsibility. In order to protect their commercial goals in Latin America, the sugar-sweetened beverage industry practices intense lobbying at high government levels in several countries across the region. This strategy is accompanied by corporate social responsibility programs that fund initiatives promoting physical activity. These efforts, although appearing altruistic, are intended to improve the industry's public image and increase political influence in order to block regulations counter to their interests. If this industry wants to contribute to human well being, as it has publicly stated, it should avoid blocking legislative actions intended to regulate the marketing, advertising and sale of their products. © Faculdade de Saúde Pública da Universidade de São Paulo.